2016
DOI: 10.3381/15-047
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY OFRALSTONIA SOLANACEARUMPOPULATIONS AFFECTING TOBACCO CROPS IN NORTH CAROLINA

Abstract: One hundred eighty four strains of Ralstonia solanacearum isolated in 2007 and 2008 from 11 tobacco fields in North Carolina were evaluated for genotypic diversity and aggressiveness. All strains were race 1, biovar 1, and belonged to phylotype II. Genetic diversity of the strains was assessed with the use of repetitive sequence-based polymerase chain reaction. DNA primers (REP, ERIC, and BOX) were used to generate genomic fingerprints. Both REP and BOX revealed 3 patterns: A r , C r , and D r and A b , C b , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Bocsanczy et al (2012) found R. solanacearum strains from tomato that were able to produce wilt symptoms at 18°C in Florida. Our growth chamber study indicated that a minimum temperature of 15°C is required for BW symptom development in tobacco cultivars with R. solanacearum strains of phylotype II collected from North Carolina (Katawczik et al 2016). Thus R. solanacearum strains may exhibit variable level of infection efficacy based on the location of isolation and other geographic factors that determine adaptability as suggested by Bocsanczy et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bocsanczy et al (2012) found R. solanacearum strains from tomato that were able to produce wilt symptoms at 18°C in Florida. Our growth chamber study indicated that a minimum temperature of 15°C is required for BW symptom development in tobacco cultivars with R. solanacearum strains of phylotype II collected from North Carolina (Katawczik et al 2016). Thus R. solanacearum strains may exhibit variable level of infection efficacy based on the location of isolation and other geographic factors that determine adaptability as suggested by Bocsanczy et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains and inoculum preparation R. solanacearum strains 4, 7, 25, and 46 previously characterized as race 1 biovar 1 phylotype II (Katawczik et al 2016;Katawczik and Mila 2012), were used. All strains were collected in North Carolina in 2007 from stems of diseased tobacco plants by isolating on tetrazolium chloride medium (TZC) (Kelman 1954) and stored in 20 % glycerol at −80°C.…”
Section: Tobacco Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, repetitive element sequence (rep)-based PCR, based on repetitive extragenic palindromic sequences (REP-PCR), enterobacterial repetitive intergenic consensus sequences (ERIC-PCR) and BOX elements (BOX-PCR) use primers to amplify conserved repetitive DNA sequences present in Gram-negative bacteria. In addition to unveiling interspecific diversity, these repetitive elements are useful for elucidating relationships within bacterial species because their fingerprints are conserved at the pathovar and strain intraspecific levels (Katawczik et al, 2016;Zulperi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…I will limit myself to analysis which can be derived from the one definition of the Disease Index (see Material and Methods), however, different definitions have been used in the literature. For example, Katawczik et al (2016) use a weighted measurement of disease incidence and perform an analysis in a generalized linear framework.…”
Section: Introductionmentioning
confidence: 99%